The Limits of Market-Based Risk Transfer and Implications for Managing Systemic Risks - Blancher, Nicolas; Haas, Francois; Khadarina, Oksana; Kiff, John. (Washington, D.C. : International Monetary Fund, 2006)
The paper discusses the limits to market-based risk transfer in the financial system and the implications for the management of systemic long-term financial risks. Financial instruments or markets to transfer and better manage these risks across institutions and sectors are, as yet, either nascent or nonexistent. As such, the paper investigates why these markets remain "incomplete." It also explores a range of options by which policymakers may encourage the development of these markets as part of governments' role as a risk manager.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet